2021
DOI: 10.2166/wcc.2021.158
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of urbanization and climate change on water quantity and quality in the Carp River watershed

Abstract: Pressure on water resources has reached unprecedented levels during the last decades because of climate change, industrialization, and population growth. As a result, vulnerability to inappropriate water availability and/or quality is increasing worldwide. In this paper, a Soil & Water Assessment Tool (SWAT) model of the Carp river watershed located in the city of Ottawa, Ontario was calibrated and validated. The model was then used to evaluate the individual and coupled impacts of urbanization and climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…They concluded that variability of the mentioned water quality parameters may change the ecosystem services of the basin, hence, adaptive management may need to be applied in the region. Zango et al (2021) assessed the impacts of urbanization and climate change on the river runoff as well as water nitrogen and phosphorus loads in the Carp Watershed, Ontario, Canada. They concluded that the urbanization and climate change impacts vary substantially depending on the geographic location and spatial scale.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that variability of the mentioned water quality parameters may change the ecosystem services of the basin, hence, adaptive management may need to be applied in the region. Zango et al (2021) assessed the impacts of urbanization and climate change on the river runoff as well as water nitrogen and phosphorus loads in the Carp Watershed, Ontario, Canada. They concluded that the urbanization and climate change impacts vary substantially depending on the geographic location and spatial scale.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Soil and Water Assessment Tool (SWAT) is a semi-distributed, physically based hydrological model that can be used to describe surface, root zone, groundwater, and stream processes (Arnold et al 1998). The SWAT model is now widely used in many watersheds throughout the world to study the impact of climate change and land use on runoff (Yang et al 2019;Hajihosseini et al 2020) and water quality (Delia et al 2021;Zango et al 2022). However, its analytical ability in assessing the sensitivity of water quality to climate change and land use is discussed relatively scarcely in the existing studies.…”
Section: Introductionmentioning
confidence: 99%
“…Landscape patterns are the distribution patterns and composite structures of landscape units in the space in different numbers, types, densities, and configurations (Turner 1990;Hu 2003), which are influenced by both natural and anthropogenic factors, which in turn restrict various ecological processes, thus further influencing the social and economic aspects of the region (Hao et al 2017;Hashem et al 2019). Quantitative studies of landscape patterns often use the landscape pattern index directly related to land use (Alberti 2005), or evaluate the resources and environmental status of the research area (Guiamel & Lee 2020) and forecast the future development (Gao et al 2021;Zango et al 2021) by various kinds of assessment and prediction model. The scope of study includes watersheds (Nuanchan et al 2015;, deserts (Duan et al 2012), wetlands (Gong et al 2011), etc., delimited by ecological scope, as well as provinces and municipalities delimited by administrative or territorial scope, and countries (Zhao et al 2007;Cirelli & Vineri 2014;Burgalassi & Luzzati 2015;Li & Qi 2019).…”
Section: Introductionmentioning
confidence: 99%